The moderating impact of concentrated ownership on related party transactions and firm performance in the Malaysian context - Alquhaif Abdulsalam Saad (Financial Internet Quarterly)
This study investigates the impact of related party transactions (RPTs) on firm performance, with a focus on the moderating role of concentrated ownership in an emerging market context. The Random effect regression was utilized for Malaysian-listed firms from 2015 to 2019 to test these assumptions. The findings reveal that RPTs are negatively correlated with firm performance, suggesting that such transactions are often motivated by expropriation concerns rather than transaction-cost efficiency. However, concentrated ownership plays a crucial governance role by mitigating the adverse effects of RPTs, thereby improving firm performance. Companies with concentrated ownership structures are better equipped to monitor and manage RPTs, reducing agency costs and opportunistic behavior. This study contributes to the literature on corporate governance by highlighting the importance of ownership concentration in alleviating the negative consequences of excessive RPTs, especially in markets characterized by high information asymmetry. The findings have significant policy implications, as they suggest that regulators should strengthen disclosure requirements and provide greater oversight of RPTs to protect minority shareholders. Future research could explore how the relationship between RPTs, ownership concentration, and firm performance evolves over time, particularly in the post-COVID-19 period, when market conditions and corporate governance practices have undergone significant changes.